SARS-CoV-2 Direct Detection Without RNA Isolation With Loop-Mediated Isothermal Amplification (LAMP) and CRISPR-Cas12 - Garcia-Venzor, Alfredo; Rueda-Zarazua, Bertha; Marquez-Garcia, Eduardo; Maldonado, Vilma; Moncada-Morales, Angelica; Olivera, Hiram; Lopez, Irma; Zuñiga, Joaquin; Melendez-Zajgla, Jorge (Frontiers in Medicine, 2021)
As to date, more than 49 million confirmed cases of Coronavirus Disease 19 (COVID-19) have been reported worldwide. Current diagnostic protocols use qRT-PCR for viral RNA detection, which is expensive and requires sophisticated equipment, trained personnel and previous RNA extraction. For this reason, we need a faster, direct and more versatile detection method for better epidemiological management of the COVID-19 outbreak. In this work, we propose a direct method without RNA extraction, based on the Loop-mediated isothermal amplification (LAMP) and Clustered Regularly Interspaced Short Palindromic Repeats-CRISPR associated protein (CRISPR-Cas12) technique that allows the fast detection of SARS-CoV-2 from patient samples with high sensitivity and specificity. We obtained a limit of detection of 16 copies/µL with high specificity and at an affordable cost. The diagnostic test readout can be done with a real-time PCR thermocycler or with the naked eye in a blue-light transilluminator. Our method has been evaluated on a small set of clinical samples with promising results.